The socioeconomic profile of the program beneficiaries Crediamigo in Juazeiro-Ce - FÃbio Ricarte BenÃcio (2012)
The policy of Microcredit has been disseminated in several countries as a strategy to combat poverty and informality, generating jobs and income through the provision of credit to microentrepreneurs at the base of the social pyramid. In Brazil, the productive microcredit program called Crediamigo implemented by Bando in northeastern Brazil, has been increasing, accumulating in his fifteen years of operation about eleven million operations, spending more than dose billion reais. Given these possibilities offered by this tool, this study aims at identifying the socioeconomic profile of program beneficiaries in Crediamigo Juazeiro-EC. For this, we analyzed the microcredit program "Crediamigo" from 2001 to 2011 in Juazeiro- EC. Featuring customers, identifying the change in their conditions of living and working, the degree of formalization of enterprises, employment generation, the allocation of resources obtained from the program and the determinants of improved living conditions of the entrepreneur as also the formalization of the enterprise. In preparing this paper the data used are primary and secondary in nature. It may be noted that major share of the customers of this program is female, aged from 30 to 40 years, there is a predominance of commercial activity followed by industrial, low level of formalization, stabilization and recruitment of workers, improving conditions living and working and successful entrepreneur. Regarding the factors that contribute to improving the living conditions of the clients of this program, there is a successful entrepreneur, your gender and ownership of the property where the shop is located.